An Antibacterial-Loaded PLA 3D-Printed Model for Temporary Prosthesis in Arthroplasty Infections: Evaluation of the Impact of Layer Thickness on the Mechanical Strength of a Construct and Drug Release - Carlos Tamarit-Martínez; Lucía Bernat-Just; Carlos Bueno-López; Adrián M. Alambiaga-Caravaca; Virginia Merino; Alicia López-Castellano; Vicent Rodilla (MDPI AG, 2024)
Infections are one of the main complications in arthroplasties. These infections are difficult to treat because the bacteria responsible for them settle in the prosthesis and form a biofilm that does not allow antimicrobials to reach the infected area. This study is part of a research project aimed at developing 3D-printed spacers (temporary prostheses) capable of incorporating antibacterials for the personalized treatment of arthroplasty infections. The main objective of this research was to analyze the impact of the layer thickness of 3D-printed constructs based on polylactic acid (PLA) for improved treatment of infections in arthroplasty. The focus is on the following parameters: resistance, morphology, drug release, and the effect of antibacterials incorporated in the printed temporary prostheses. The resistance studies revealed that the design and layer thickness of a printed spacer have an influence on its resistance properties. The thickness of the layer used in printing affects the amount of methylene blue (used as a model drug) that is released. Increasing layer thickness leads to a greater release of the drug from the spacer, probably as a result of higher porosity. To evaluate antibacterial release, cloxacillin and vancomycin were incorporated into the constructs. When incorporated into the 3D construct, both antibacterials were released, as evidenced by the growth inhibition of Staphylococcus aureus. In conclusion, preliminary results indicate that the layer thickness during the three-dimensional (3D) printing process of the spacer plays a significant role in drug release.